Capacitive deionization on-chip as a method for microfluidic sample preparation1. Issue 6 (21st March 2015) - Roelofs, Susan H.; Kim, Bumjoo; Eijkel, Jan C. T.; Han, Jongyoon; van den Berg, Albert; Odijk, Mathieu
<x xml:space="preserve">Abstract</x> We demonstrate capacitive deionization in a microfluidic chip and monitor the salt concentration between the desalination electrodes in real-time.